Poligami Sebagai Solusi Perselingkuhan - Wafie, Slamet Ahmad; Qosiimah, Fenti Zya Ain Salwa; Nabila, Vania Rahma (LPPM UNU BLITAR, 2025)
Polygamy as a solution to infidelity has become a topic of interest in the social and legal context in Indonesia. In this study, the author highlights the rampant infidelity that occurs due to free social patterns, which shows the urgency of polygamy as an alternative to building a legitimate relationship. In Indonesia, polygamy is legally regulated in the 1974 Law on Marriage and the Compilation of Islamic Law (KHI), which provides the basis for this practice, especially in situations where the wife cannot carry out her obligations. Islam allows polygamy in certain circumstances on condition that it is fair. Although there is much controversy about polygamy, the author argues that polygamy has many benefits that need to be understood by society. However, the minimal and negative understanding of polygamy among Indonesian society often makes people prefer to have affairs rather than consider polygamy as a solution. This study uses a library method to examine the wisdom of tasyri'iyah from polygamy as a solution to infidelity in the modern era. By providing education about the values of benefits in polygamy, it is hoped that it can reduce the number of infidelity and improve the quality of relationships in the household and society as a whole.